PERANCANGAN MESIN PENCACAH RUMPUT GAJAH UNTUK PETERNAK DESA BALEKEMBANG KECAMATAN NAGRAK KABUPATEN SUKABUMI - WIDIANTO, EKO; Kadarismansyah; Mulyadi (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2021)
The design of the elephant grass chopper machine to make it easier for cattle breeders to chop elephant grass quickly and efficiently. This elephant grass chopper/machine serves to chop elephant grass into pieces. The process of designing this elephant grass chopper machine or tool includes several stages, namely image design, material selection, measurement, cutting, welding formation, painting and the last is the finishing process. In the process of designing a machine or tool for chopping elephant grass, basically the materials used are plate iron, elbow iron and axle iron. The material is used because it is adjusted to the needs of the object to be made, then the material is measured to be cut using a cutting wheel cutting machine, the use of this machine serves to obtain good cutting results. After the material is cut, the next process is welding and assembling the material. In this process the welding used is SMAW welding. The last stage is the finishing process. In this process, objects that have been formed or finished are ground, sanded and puttyed to flatten the parts of the former welding process. The dimensions of this elephant grass chopper are 1000mm high, 750mm long and 600mm wide. It has a 1HP dynamo motor as its driving force with a speed of 1400 Rpm.